Contribution of semiquantitative analysis with dynamic contrast enhanced magnetic resonance imaging to the differential diagnosis of focal liver lesions - Düzkalır, Hanife Gülden; Kış, Naciye; Urgun, Deniz Akay; Ağaçlı, Mehmet Oğuzhan; Kılıçoğlu, Zeynep Gamze (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. We aimed to evaluate the usefulness of dynamic contrast-enhanced (DCE) MRI semiquantitative analysis values in focal liver lesions (FLL) to provide additional qualities that can be used in daily practice in the differential diagnosis of lesions. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This retrospective study included 91 patients with liver masses on DCE-MRI. The sensitivity and specificity of time intensity curves (TIC) and semiquantitative analysis values were evaluated to differentiate benign and malignant lesions. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The study included 91 patients (376 lesions), aged between 28-81 years. Of the lesions, 303 were malignant and 73 were benign. In TIC semiquantitative analysis, it was found that “Tpeak” and “wash-out” rate values showed differences, especially in the differentiation of HCC, metastasis, and hemangioma. Area under curve, maximum relative enhancement, and “wash-in” and “wash-out” values of metastases and hemangiomas were different. Brevity of enhancement values of HSK, hemangiomas, and metastases were found to be different. The risk of malignancy was found to be high when the “wash-out” ratio was above 0.08 (sensitivity: 64.3%, specificity: 70.4%). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. We think that the 0.08 threshold value we found for the washout ratio with DCE-MRI semiquantitative analysis data will be useful in daily practice in the differentiation of malignant and benign FLL.